Relação entre uniformidade da produtividade e indicadores de uniformidade da irrigação em sistema de irrigação por microaspersão em citros - Da Silva Junior, Helio Moreira; Gomes, Anthony Wellington Almeida; Costa, Cicero Teixeira Silva; Saad, João Carlos Cury [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2017)
One of the recommended design criteria for localized irrigation systems is based on the desired emission uniformity, assuming that the uniform water application generates uniform production. The aim of this study was to evaluate the relation between the project emission uniformity and yield uniformity, in microsprinkler irrigation system. A Linear Programming model was applied in the irrigation system design of a citrus orchard.The sensitivity analysis involved different slopes, 0, 3, 6, 9 and 12%, and different values of emission uniformity, 60, 70, 75, 80, 85, 90 and 94%. The emitter discharge uniformity increased with the increase of the slope, except at 12%. It was observed, in all the combinations evaluated, that the productivity variation coefficient decreased when the water production function was used. The pressure head variation coefficient ranged from 2 to 33%, the flow variation coefficient ranged from 1 to 17%, and yield variation coefficient with 60 days of irrigation ranged from 0,03 to 1,25%. In order to obtain high yield with high uniformity in the operational unit, it is necessary to consider not only the emission uniformity, but especially the appropriate choice of the irrigation depth.
Relationship between citrus productivity and indicators of niformity in trickle irrigation system
Keywords: Emission uniformity; Microsprinkler; Orange tree